232k views
0 votes
Solve using elimination method x-3y=1 and 2x+5y=6​

1 Answer

4 votes

Answer:

x =23/11, y =4/11

Explanation:

subtract equation 1 from equation 2

2x-x + 5y-(-3) =6-1

x + 8y = 5

make x the subject of formula

x = 5-8y(equation#)

substitute x = 5-8y in equation 1

5-8y-3y = 1

5-11y = 1

collect like terms

5-1 = 11y

4= 11y

divide both sides by 11

4/11 = 11y/11

y = 4/11

put y = 4/11 in equation #

x = 5-8(4/11)

x = 5-32/11

LCM= 11

x = 55-32/11

x = 23/11

so, x =23/11, y = 4/11

User JeffRSon
by
5.8k points